Produksi Air Bersih di Ma’had Rizqullah Desa Simpang Sungai Duren Kecamatan Jambi Luar Kota Muara Jambi - Ahmad Riduan; Rainiyati Rainiyati; Sarah Fiebrina Heraningsih; Dian Ariansyah (Jurnal Pengabdian Pada Masyarakat, 2019)
CLEAN WATER PRODUCTION IN RIZQULLAH ISLAMIC BOARDING SCHOOL JAMBI. Pondok Pesantren is an Islamic boarding school where students are learning about Islam as well as science and technologies. Adequate and good quality of facilities and infrastructures are needed to support good teaching and learning process. One of such facilities is clean and healthy water which is important to students and teachers in the Pondok Pesantren. Bad quality of water, either for washing or drinking, will affect students’ concentration in studying. Therefore, our community service project was aimed at improving the quality of water at Ma’had Rizqullah by installing a clean water system using multilevel filtration method. The water to be processed was ground water collected from bore wells in Pondok area. By this technology, the requirement of clean water in Ma’had Rizqullah can be met, al can also supply water needs for community around the Pondok. The product of this technology was clean water that can be used for daily activities by students and teachers living in Pondok and surrounding people.